2014
DOI: 10.1155/2014/192376
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Preferred Health-Seeking Institutions among Rural Elderly Individuals with and without Chronic Conditions: A Population-Based Study in Guangdong Province, China

Abstract: The aim of this study was to examine health-related quality of life (HRQL) as measured by SF-36 and to identify these factors and the preferred health-seeking institutions of 12,800 persons aged 60 and older with and without chronic conditions in rural areas of Guangdong Province by multistage stratified cluster sampling method. HRQL among rural elderly subjects with chronic conditions was lower than that of elderly subjects with no chronic conditions. Multiple linear regression showed that marital status, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
3
18
1
Order By: Relevance
“…The increase in the psychological concentration was positively correlated with the increased likelihood of developing NCDs, and those who had a better relationship with their neighbours were more likely to suffer from major NCDs. Similarly, some studies on negative social exchange suggested that the presence of social relationships may actually add stress to a person’s life rather than reduce it, especially if the relationship is too demanding, insensitive and interfering, or if those with whom one is in contact suffer from serious problems of their own [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the psychological concentration was positively correlated with the increased likelihood of developing NCDs, and those who had a better relationship with their neighbours were more likely to suffer from major NCDs. Similarly, some studies on negative social exchange suggested that the presence of social relationships may actually add stress to a person’s life rather than reduce it, especially if the relationship is too demanding, insensitive and interfering, or if those with whom one is in contact suffer from serious problems of their own [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low quality of sleep may affect immune system, the ability to function and social activities, and may have an impact on physical and mental health in HRQoL [ 33 ]. The impact of chronic conditions in general populations was reflected more in PCS than in MCS scores [ 15 ]. Compared to the rural areas, adequate health information and knowledge, higher level of basic infrastructure, higher incomes, availability of health services may help urban residents prevent chronic diseases in northeast China [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL has also been measured for health management and clinical advices of chronic diseases [ 11 14 ]. Elderly adults’ HRQoL were focused on different conditions for the reason that the aging group has expanded tremendously in decades worldwide especially in China, the largest population scale worldwide [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progressive rise in life expectancy contributes to an increase in the prevalence of chronic illnesses such as Muscular pain, joint pain, restlessness, headache, visual problems, and high blood pressure, cardiovascular disease, digestion and stomach problems, diabetes in the elderly population ( Zhou, C. Wang, Yang, Z. Wang, Zheng, & J. Wang, 2014 ).These disorders and many other health problems are result of poor health and unsanitary practices…”
Section: Introductionmentioning
confidence: 99%